Using visual arts in the young learner classroom: exploring the effect on engagement - Litvinova, Ekaterina Aleksandrovna (2019)
This report is based on action research carried out in a first cycle English classroom of a Portuguese school. Two types of visual arts: paintings and drawings were taken as a basis for PowerPoint presentations that were incorporated into the lessons. The effect on student engagement was compared to that from lessons based on visual arts contained in the coursebook: photographs and illustrations. Multidimensional point of view on engagement was considered in the paper, where the construct of engagement is constituted by emotional, cognitive, and behavioural components. The level of engagement in terms of the three dimensions was evaluated with the help of four tools, two direct: questionnaires and interviews with the students, and two indirect: observation grids and a teaching journal. Selection of visual arts to be used in the young learner classroom was described and the most engaging materials and activities based on visual arts are outlined. The outcomes showed that student engagement was stimulated to a greater degree by paintings and drawings than by photographs and illustrations.